2016
DOI: 10.1002/cam4.799
|View full text |Cite
|
Sign up to set email alerts
|

Secondary primary malignancies during the lenalidomide–dexamethasone regimen in relapsed/refractory multiple myeloma patients

Abstract: Lenalidomide in combination with dexamethasone (Len‐dex) represents a highly effective treatment in relapsed/refractory multiple myeloma (RRMM) patients. However, an increased risk of secondary primary malignancies (SPMs), including myelodysplastic syndrome (MDS) and acute myelogenous leukemia (AML) has been described in patients receiving lenalidomide. In order to assess the incidence and features of this complication, we reviewed 195 patients with RRMM treated with Len‐dex at our institution. The median foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…Previous studies have described an increased risk of SMPs in MM patients, notably the development of MDS/AML . The association between the development of TRM neoplasms and the treatment with lenalidomide in patients with MM is a matter of debate, with contradictory results reported . Differences in the design of these studies might account for those discrepancies, with the lack of SPMs incidence/follow‐up in those cases in which lenalidomide was discontinued, as the major limitation in the clinical trial setting.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have described an increased risk of SMPs in MM patients, notably the development of MDS/AML . The association between the development of TRM neoplasms and the treatment with lenalidomide in patients with MM is a matter of debate, with contradictory results reported . Differences in the design of these studies might account for those discrepancies, with the lack of SPMs incidence/follow‐up in those cases in which lenalidomide was discontinued, as the major limitation in the clinical trial setting.…”
Section: Discussionmentioning
confidence: 99%
“…According to our data, complex karyotype is the most frequently alteration in TRM malignancies in patients treated for a previous MM. In another population‐based study focused on SPMs during the lenalidomide‐dexamethasone regimen in relapsed/refractory MM patients 5 out of 6 patients who developed a therapy related AML/MDS had complex cytogenetics . With regard to survival, in a previous large population‐base study of MM patients the median time of survival after diagnosed AML/MDS was 2.4 months ,.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies, including an analysis of pooled data from 11 clinical trials of lenalidomide-based therapy involving 3846 patients with relapsed refractory multiple myeloma (RRMM) reported an incidence ratio (IR) of 3.36 for all SPMs and 2.08 for all-invasive hematological malignancies [11]. Another retrospective study with 195 patients showed the incidence of myelodysplastic syndrome (MDS) and acute myelogenous leukemia (AML) as 1.29 and 1.08, respectively [12-13]. The overall median time of diagnosis of SPMs is 28 months for hematological and 15 months for solid tumors [13-14].…”
Section: Discussionmentioning
confidence: 99%
“…In the era of immunomodulating drugs (imids) and especially lenalidomide, Reece and Goswami reported MDS/AML in 2.6% of patients treated with lenalidomide for refractory/relapsed MM, at a median of 76 months from the time of MM diagnosis [6]. An even longer delay was reported very recently by the same group in a single institution, with a median time from diagnosis to MDS/ AML appearance of 6.7 years [7]. occurred very rapidly, barely 2 years after auto-SCT.…”
Section: Discussionmentioning
confidence: 99%